2019
DOI: 10.3846/btp.2019.44
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Policies and Attitudes Towards the Performance of Older Employees in Lithuania

Abstract: The ageing labour force is the one of the main challenges for the labour market in Lithuania. The working career of older employees very much depends on the policies and attitude of employers. Thus, the aim of this paper is to analyse the policies and attitudes of Lithuanian employers towards older employees. The data of Eurobarometer 76.2 in 2011 and the data of the employers’ survey in Lithuania in 2014 were used for the implementation of the goal. The construction, trade, education, health care and public a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…We probably have someone who have left earlier but we also have someone who should have retired a long time ago. (9) There were also examples of workers who stayed longer than the stipulated retirement age:…”
Section: Retirement Ages In the Organizationmentioning
confidence: 99%
See 3 more Smart Citations
“…We probably have someone who have left earlier but we also have someone who should have retired a long time ago. (9) There were also examples of workers who stayed longer than the stipulated retirement age:…”
Section: Retirement Ages In the Organizationmentioning
confidence: 99%
“…it should be, but I think HR has been involved quite often, they (employees) have gotten into the habit of going to the HR manager to talk about such things. (9) The informants indicated that the year before the official retirement age was the most common occasion when the question of retirement was raised, usually at the yearly employee evaluation. Another approach mentioned by the informants was to send a letter to the employee, but in many cases, this was considered unpleasant or even offensive by employees.…”
Section: Transition Initiativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical review [16] showed a generally positive attitude of Lithuanian employers in construction, education, trade, health care and public administration towards agerelated employees. And retraining increases the competitiveness and demand of professionals, overcoming some outdated norms and stereotypes in employment [17].…”
Section: Introductionmentioning
confidence: 98%